Media Coverage of Immigration and the Polarization of Attitudes - Schneider-Strawczynski, Sarah; Valette, Jerome (American Economic Journal: Applied Economics, 2025)
This paper investigates the effect of media coverage on immigration attitudes. It combines data on immigration coverage in French television with individual panel data from 2013 to 2017 that records respondents' preferred television channel and attitudes
Keywords: Demographic Economics; Effects of Psychological; Indigenous Peoples; Micro-Based Behavioral Economics; Non-Labor Discrimination